Assessment of knowledge of risk factors and prevention of obesity among school children: a cross sectional study - Gunagi, Praveena R.; Karikatti, Shobha S.; Halki, Sunanda B. (International Journal Of Community Medicine And Public Health, 2019)
Background: Childhood obesity is a major contributor to the global burden of chronic diseases and is an important determinant of cardiovascular diseases, type II diabetes etc. This can largely be attributed to the transformation in the lifestyles of children. There is still lack of knowledge about obesity among high school children. Objective of this study was to assess the knowledge of risk factors of obesity among school children and to find out the knowledge of hazards and preventive measures of obesity among school children. Methods: A cross-sectional study was conducted among school students aged between 13-14 years from 9 randomly selected schools. The total sample included 480 students. Results: Out of 480 subjects 70.4% had heard about obesity, 62.3% were aware about the increasing prevalence of obesity among the youngsters, 26.7% thought unhealthy dietary factors and 29% thought mental stress were the main factors leading to obesity and non-communicable diseases. More than 75% students had correct knowledge of dietary factors associated with obesity like eating larger portion of food, eating fried foods, having junk foods. 51-75% of the students responded correctly for the factors i.e. using motorcycle for short distance. Conclusions: More than half of the students had knowledge of specific dietary and physical activity risk factors. Majority of the students identified high blood pressure, diabetes and heart problem as hazards of obesity. Only one third of the students knew preventive measures like adequate intake of fruits and vegetables, limiting unhealthy snacks and limiting screen time to prevent obesity.